Utilization of Daucus carota subsp. Sativus (Carrot) Peels and Oryza sativa (Rice) as Alternative Materials for Paper Production - Kim, Jiwoo (Animo Repository, 2022)
The problem of pollution and deforestation have continuously contributed to the mass deterioration of the environment. This study aimed to create paper from rice and carrot wastes tested in a laboratory. The study followed an experimental research design, utilizing TAPPI T-220 test methods and ISO standard procedures. The paper sheets were tested under four quality tests: paper tear index, folding endurance, grammage, and paper burst strength. Data gathered from laboratory tests were statistically analyzed via the independent t-test. It was found that rice papers had a higher paper tear index (4.99 mN.m^2/g), folding endurance (3.81 folds), and paper burst strength (1.47 kPa.m^2/g) than carrot papers (2.56 mN.m^2/g, 0.77, and 1.10 kPa.m^2/g). Carrot papers, however, had higher grammage than rice papers (152.76 g/m^2 and 132.90 g/m^2, respectively). There was no significant difference found in data for paper tear index (p = 0.072) and paper burst strength (p = 0.13), while there was a substantial difference in terms of folding endurance (p = 0.033). Previous studies have supported each result and findings. In conclusion, cooked rice can be considered a promising raw material for the paper industry. Although carrot papers were significantly weaker, they still provided average values compared to normal papers. Future research should consider exploring other interventions such as soda pulping and kraft pulping